Physico-mathematical foundations of psychodynamics - Namazi, Hamidreza (2013)
Psychodynamics as a branch of human thermodynamics contains a wide group of theories which analyze the effect of instinctive drives and forces on human behaviour. In fact, Psychodynamics considers the human personality as the result of interaction between his biological constitution and environment. Early in the development of psychodynamics, theories only talk about the effect of unconscious drives and forces. By the development of these theories, talking about conscious motivation and its interaction with unconsciousness came into account. Based on the first law of thermodynamics Freud proposed a dynamic psychology considering the human personality as the result of interaction between id (biological needs and drives), the super-ego (environment) and ego (conscious mind). Following the work done by Freud, Jung made some major contributions to psychology. This research is devoted to the study of the human brain as the processing center of energy transform in human life in order to create a macroscopic model of human consciousness. In order to achieve this goal, the fractional diffusion equations are applied to human cortex with macro level predictability of the brain response to external stimuli. In order to validate the proposed model, EEG data are applied to the model, and the results are validated versus the reference data. The results of this modelling are useful not only for the fundamental analysis of brain signals propagation, but also can be used for many types of applications such as seizure prediction by using EEG signals.